Le gouvernement de la plaine - Denis Delbaere (Développement Durable et Territoires)
This paper introduce the hypothesis that landscape is the principle of a new kind of governance, radically different from the prescriptive, voluntaristic and active way of usual ways of rulling and managing territories. More than a territorial project, Landscape governance should arouse critical and integratives (meta)projects. The paper deals with a research about the way great transport infrastructures of Likoto Eurometropolis have little by little generate aroud them non planned living spaces, that I call « urban plains ». I will show how those plains are more and more visibles, and perhaps become today a considered landscape, defended and appreciated by those who live in.